The Patterns of Islamic Education Development during the Era of Bani Umayah: Education Institution and Curriculum, and Teachers - Wahidah Wahidah; Suriadi Samsuri (Al-Misbah (Jurnal Islamic Studies), 2021)
This article aims to discuss the Islamic education during the Bani Ummayyah era. The history of Islamic Education is essentially related to the religion history. The periodization of Islamic education is always on the period of the history itself. The Islamic Education in the Prophet Muhammad SAW era is the period of Islamic education development by civilizing the education in daily lives as the Al-Qur’an teaching. The education during the period of Bani Umayyah has developed of if it is seen from their learning aspect, although the system is similar to it during the era of Prophet and khulafaur rasyidin. The method utilized in this research is Study of Literature, which is done by analyzing library sources in forms of relevant books and journals. The result indicates 1) the pattern of special education development such as Arabic nuances, Islamic foundation affirmation, naqliyah knowledge and language development, foreign language teaching, and kuttab and mosque strengthening; 2) development of the most stand out education field is in the institutions; 3) non-formal curriculum is used; and 4) there are many teacher figures and scholars who are capable in the scientific field.